Surgical-orthodontic treatment of impacted permanent canines in the mandible: two case reports - Topka, Agnieszka; Racka-Pilszak, Bogna; Wojtaszek-Słomińska, Anna; Orzelska-Blomberg, Maria (Journal of Stomatology, 2019)
Dental eruption disorders occur frequently, affecting almost 20% of the population. They include canine impaction, with an incidence of 0.9-4.3% of patients. The aim of the study was to present the authors’ experience in bringing impacted mandibular canines to the occlusal plane using fixed appliances. Two case reports of patients who presented for treatment at the Orthodontic Clinic of Medical University of Gdansk have been described. Two 11-years-old patients were orthodontically diagnosed. In both cases, impacted canines were revealed. Treatment plan included orthodontics and surgical treatment of tooth 43, so that it could be aligned into the arch. The treatment was performed with fixed straight wire appliance. The effect of treatment in both cases was good, with toot 43 its right positions. Treatment time lasted 3 and 2.5 year, respectively. Impacted mandibular canines are of rare occurrence, of which management poses therapeutic difficulties. Both aesthetics and occlusion determine the proper choice of treatment, so that the canine is brought back to the arch by using surgical and orthodontic extrusion. In order to minimize the risk of complications, early diagnosis is necessary as well as close interdisciplinary cooperation of an orthodontist and surgeon.